2015
DOI: 10.1089/lgbt.2014.0082
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Weight, and Health Among Adult Lesbian and Bisexual Women: A Metasynthesis of the Multisite “Healthy Weight Initiative” Focus Groups

Abstract: An unsolicited, overarching theme was aging and its influence on the participants' perspectives on health and weight. Interventions should be tailored to the needs, goals, and community norms of LB women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…LGBT people in general (Rothblum, 2014). The basis of weight discrimination comes from women having to aspire to a body size defined as thin by the media and increasingly by healthcare systems (Kumanyika et al, 2016;Garbers et al,2015). The fear of discrimination among LB women of larger size has been reported previously in focus group research (Fogel, Young, & McPherson, 2009).…”
Section: Weight Bias and Discrimination Against Lb Women With Larger mentioning
confidence: 95%
See 2 more Smart Citations
“…LGBT people in general (Rothblum, 2014). The basis of weight discrimination comes from women having to aspire to a body size defined as thin by the media and increasingly by healthcare systems (Kumanyika et al, 2016;Garbers et al,2015). The fear of discrimination among LB women of larger size has been reported previously in focus group research (Fogel, Young, & McPherson, 2009).…”
Section: Weight Bias and Discrimination Against Lb Women With Larger mentioning
confidence: 95%
“…Weight loss and reduction in waist-to-height ratio were secondary goals that were tracked with pre-and postintervention measurements, but not emphasized to participants. Education and support were provided within an LB specific context, as indicated from previous literature and our focus groups (Krakauer & Rose, 2002;Garbers et al, 2015). LB women want to feel safe and have their experiences centered in group interventions that understand their issues as sexual minority women (Krakauer & Rose, 2002).…”
Section: Weight Bias and Discrimination Against Lb Women With Larger mentioning
confidence: 99%
See 1 more Smart Citation
“…The Institutes of Medicine (U.S.) (2012) study on Accelerating Progress in Obesity Prevention guided the design of the interventions. The interventions were further tailored based on feedback from 11 focus groups, which were conducted during the formative design phase of the project (Garbers et al, 2015). Results from these focus groups indicated that the norms for the LB women's community were acceptance of women at every size, strong objections to heterosexual norms on weight, and experiences of weight discrimination by health care providers (Garbers et al, 2015).…”
mentioning
confidence: 99%
“…The interventions were further tailored based on feedback from 11 focus groups, which were conducted during the formative design phase of the project (Garbers et al, 2015). Results from these focus groups indicated that the norms for the LB women's community were acceptance of women at every size, strong objections to heterosexual norms on weight, and experiences of weight discrimination by health care providers (Garbers et al, 2015). Although the HWLB program was conceived to address obesity in the LB population, based on focus group feedback, promotional material for the study focused on healthy choices as reflected in the following goals to 1) increase consumption of fruits and vegetables, 2) decrease consumption of sugar-sweetened beverages (SSBs), 3) decrease consumption of alcoholic beverages, 4) increase physical activity minutes (2 measures), and 5) increase physical and mental quality of life (2 measures).…”
mentioning
confidence: 99%